Poor embryo development and preimplantation genetic diagnosis outcomes of translocations involving chromosome 10: Do we blame genetics?. Issue 5 (October 2015) - Tulay, P.; Gultomruk, M.; Findikli, N.; Bahceci, M.
Summary Balanced reciprocal translocation carriers are usually phenotypically normal. Although the reproductive risk of these carriers varies, they generally have a lower chance to produce normal or balanced gametes. Preimplantation genetic diagnosis (PGD) is offered to these patients to increase their chances of becoming pregnant by selecting a balanced embryo for transfer. This study aimed to analyse the development and the PGD outcome of the embryos obtained from reciprocal translocation carriers focusing on ones with chromosome 10 rearrangements. In total, 27 reciprocal translocation carriers underwent 31 cycles of PGD. PGD was performed using multicolour fluorescence in situ hybridisation for 298 embryos and of these 136 were obtained from couples carrying translocations involving chromosome 10 rearrangements. Carriers of translocations involving chromosome 10 rearrangements have a lower chance of producing normal or balanced embryos compared with the carriers with other rearrangements. The development of embryos obtained from the patients with chromosome 10 rearrangements was impaired and only a limited number of embryos developed to the blastocyst stage.